Assessment of employment conditions in the library workplace: A comparative study of public and private universities in Kwara State, Nigeria - Atunde, Martins; OLADIMEJI , Rasheedat; ABDULRAHEEM, Jamiu; MEDUPIN, Johnson; TIJANI, Abdulganiyu; OLADEJOBI, Janet; RILWAN, Abayomi; JESUWAYE, Olusanmi (Journal of Interdisciplinary Research (ISSN: 2408-1906), 2021)
The study comparatively assessed employment conditions in the library workplace focusing on public and private universities in Kwara State, Nigeria. The descriptive research of a cross-institutional survey was adopted. A sample of 160 research subjects from four universities (2public and 2 private) were sampled through multi-stage sampling of purposive, and stratified random sampling methods. A 25-item validated, pretested and administered questionnaire was used for data collection. Data collected were analysed with appropriate descriptive and inferential statistical tools, such as, mean, standard deviation and t-test statistics. Result revealed that professional development opportunities and quality work-life integration were better in public University libraries than what is enjoyed in their private counterpart, while pay and compensation, promotion prospects and welfare benefits in private University libraries are better than what is obtained in public University libraries. The study suggested that employment conditions differential exists in public and private University libraries in Kwara State, Nigeria.